What characteristics a clinical CSF system has to have? - Colombo, Elisa; Issolio, Luis; Santillan, Javier; Aguirre, Rolando (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
We discuss the characteristics a system to measure the contrast sensitivity function (CSF) in the ophthalmologic clinic has to have. We propose that this system should be computer based in order to assure flexibility and precision. Besides the original calibration, this equipment needs an auxiliary system to keep the working conditions allowing periodical gamma corrections. We try a calibration method based on visual comparisons and show that it is valid and simple. We propose to use an adaptive psychophysical method to obtain contrast thresholds that assure a good compromise between precision and duration of the whole test. Finally, we propose that the system has to have its own normality curves for the different age ranges allowing the practitioner to perform clinical evaluations. Summing up, we can say that taking into account the above issues, the fidelity of the stimuli will be guaranteed and the challenges entailed in its transference to the clinic will be overcome.
Optica Applicata, Vol. 39, 2009, nr 2, s. 415-428
Keywords: optyka; contrast sensitivity; ophthalmologic clinic; standards